2022
DOI: 10.1177/14648849221080356
|View full text |Cite
|
Sign up to set email alerts
|

How to tackle the conceptual inconsistency of audience engagement? The introduction of the Dynamic Model of Audience Engagement

Abstract: Scholars repeatedly argue that ‘audience engagement’ as a concept and, consequently as a practice, remain inconsistent and ambiguous. Such conceptual inconsistency is in tension with the relevance that the phenomenon of audience engagement has gained in contemporary discussions about journalism. In this article, we tackle the conceptual inconsistency of audience engagement by conducting a qualitative examination of all academic peer-reviewed publications (217) that dealt with ‘audience engagement’ and interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Most studies define consumption as the level of exposure to news (Yang & Patwardhan, 2004), while others describe it as news-use habits (Van Dijk, 2006) (Matthews, 2022;Su et al, 2022;Vogler et al, 2023). The literature showed that individuals' engagement with social media news differs from other types of news consumption because it can take various forms, with some being more active than others (Dvir-Gvirsman, 2022; Gajardo & Costera Meijer, 2022). According to Molyneux (2019), the more platforms a person uses to obtain news, the higher their levels of engagement.…”
Section: Affective Vs Cognitive News Engagementmentioning
confidence: 99%
“…Most studies define consumption as the level of exposure to news (Yang & Patwardhan, 2004), while others describe it as news-use habits (Van Dijk, 2006) (Matthews, 2022;Su et al, 2022;Vogler et al, 2023). The literature showed that individuals' engagement with social media news differs from other types of news consumption because it can take various forms, with some being more active than others (Dvir-Gvirsman, 2022; Gajardo & Costera Meijer, 2022). According to Molyneux (2019), the more platforms a person uses to obtain news, the higher their levels of engagement.…”
Section: Affective Vs Cognitive News Engagementmentioning
confidence: 99%
“…In academic literature, participation is often linked to empowerment of citizens being able to influence news agendas (Reese, 2019; Timmermans et al, 2011), the quality it can bring and the new journalistic revenue model, but also to the concerns voiced by journalists. In comprehensive literature reviews, Engelke (2019), Borger et al (2013) and Gajardo and Costera Meijer (2022) show that research is quite limited in understanding the role of the audience in news production. Our first goal in the literature review is to analyze which levels of participation can be discerned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is relevant as there are different degrees of non-participation, depending on the extent to which news user can influence or modify journalistic content, the resources required, such as knowledge, time, and technological expertise, and the required (creative) effort (Loosen and Schmidt, 2012; Picone et al, 2019). Our distinction starts from the perspective of the user and therefore contrasts with the existing production-oriented approaches (Domingo et al, 2008; Gajardo and Costera Meijer, 2022; Jönsson & Ornebring, 2011).
Figure 1.The four levels of participation in journalism.
…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increasingly intense digital and social transformation has further driven audience fragmentation and media content consumption across multiple screens and platforms over the last years, to such an extent that some publics no longer consume media in the conventional ways. Recent research suggests that the difficulty involved in attracting the attention of distracted audiences, who are comfortable migrating between different screens and platforms, has prompted growing concern over finding ways to enhance audience engagement levels and seeking emotional connection (Berguillos, 2017;Chan-Olmsted & Wolter, 2018;Edlom, 2022;Gajardo & Costera, 2022;Kleer & Kunz, 2021).…”
Section: Introductionmentioning
confidence: 99%